2019
DOI: 10.1002/cyto.a.23944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flow‐Induced Microfluidic Chip Wall Deformation on Imaging Flow Cytometry

Abstract: Imaging flow cytometry is a powerful tool by virtue of its capability for high‐throughput cell analysis. The advent of high‐speed optical imaging methods on a microfluidic platform has significantly improved cell throughput and brought many degrees of freedom to instrumentation and applications over the last decade, but it also poses a predicament on microfluidic chips. Specifically, as the throughput increases, the flow speed also increases (currently reaching 10 m/s): consequently, the increased hydrodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Although Raman flow cytometry (RFC) is known as a high-throughput and non-invasive method for mapping the distribution of distinct molecular groups in live cells, [15][16][17] it requires huge optical equipment, a complicated setup, and strict experimental conditions, such as three-dimensional (3D) cell focusing techniques for reproducible detection signals, 18 relatively low flow rates for high-quality imaging 15 and optical transmission of channel materials for light detection. [19][20][21] As an alternative, impedance cytometry has the potential to characterize intracellular components of single cells in a label-free manner. Xu et al theoretically demonstrated that impedance cytometry can characterize the components within the cellular membrane at high frequencies (typically >1 MHz) based on a single shell model, 22 as a highfrequency electric field can cross the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Although Raman flow cytometry (RFC) is known as a high-throughput and non-invasive method for mapping the distribution of distinct molecular groups in live cells, [15][16][17] it requires huge optical equipment, a complicated setup, and strict experimental conditions, such as three-dimensional (3D) cell focusing techniques for reproducible detection signals, 18 relatively low flow rates for high-quality imaging 15 and optical transmission of channel materials for light detection. [19][20][21] As an alternative, impedance cytometry has the potential to characterize intracellular components of single cells in a label-free manner. Xu et al theoretically demonstrated that impedance cytometry can characterize the components within the cellular membrane at high frequencies (typically >1 MHz) based on a single shell model, 22 as a highfrequency electric field can cross the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of this research, we easily made a perforated PDMS microchannel which is difficult to fabricate with the mold replica method, especially in the case of thin PDMS layer. Based on the high mechanical strength and optical stability of the G-P-G configuration, we expect that the application we made be utilized in digital PCR applications and optical microfluidic systems such as biochips equipped with a high-speed camera [ 38 , 39 ] or laser-assisted reactive chamber usages.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these glass properties and fundamental technologies, many unique applications such as detection by Raman microscopy, 12 thermal lens microscopy, 13 organic synthesis, 14,15 gas analysis, 16,17 cell patterning and analysis, 18,19 electrophoretic separations, 20 nanostructurebased molecule separations 21,22 and cell analysis by ultra-fast flow imaging 23 have been developed. These applications are difficult to realize with polymer-based microfluidic devices because polymers show lower performance of light transmission, chemical stability against organic solvents, retaining gas in microchannels, have lower values of Young's modulus which is a fundamental factor in cell scaffolding, and are less suitable for precise fabrication at microscale than glass does.…”
Section: Introductionmentioning
confidence: 99%